2009
DOI: 10.1152/ajprenal.00112.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced F-actin reorganization in endothelial cells involves RhoA activation

Abstract: Acute ischemic kidney injury results in marked increases in local and systemic cytokine levels. IL-1alpha, IL-6, and TNF-alpha orchestrate various inflammatory reactions influencing endothelial permeability by altering cell-to-cell and cell-to-extracellular matrix attachments. To explore the role of actin and the regulatory proteins RhoA and cofilin in this process, microvascular endothelial cells (MS1) were exposed to individual cytokines or a cytokine cocktail. Within minutes, a marked, time-dependent redist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…The actin filaments are known to form a network under the cell membrane providing mechanical strength and to undergo extensive remodeling and reorganization upon TNF-α stimulation. [34][35][36] The observed increase in filament density could explain the higher stiffness of the stimulated cells as compared with the controls. Also, the level of expression of ICAM-1 was measured through ELISA, demonstrating a statistically significant increase in the surface density for these adhesive molecules (Figure 4), normally overexpressed on the inflamed endothelium.…”
Section: Effects Of Tnf-α Stimulation On the Apparent Elastic Modulusmentioning
confidence: 89%
“…The actin filaments are known to form a network under the cell membrane providing mechanical strength and to undergo extensive remodeling and reorganization upon TNF-α stimulation. [34][35][36] The observed increase in filament density could explain the higher stiffness of the stimulated cells as compared with the controls. Also, the level of expression of ICAM-1 was measured through ELISA, demonstrating a statistically significant increase in the surface density for these adhesive molecules (Figure 4), normally overexpressed on the inflamed endothelium.…”
Section: Effects Of Tnf-α Stimulation On the Apparent Elastic Modulusmentioning
confidence: 89%
“…Indeed, both IL-1β [43][44][45] and TNF-α [46][47][48] have been shown to induce F-actin reorganization in a variety of cell types, but further changes of cell mechanical properties remain controversial. Qi et al [49] reported a decrease of tenocyte stiffness (cellular level) but an increase of tendon stiffness (tissue level) [50] in response to IL-1β; Bakker et al [30] showed that both IL-1β and TNF-α decreased the stiffness of osteocytes; and Lee et al [51] found that TNF-α increased the stiffness of all three endothelial cell lines tested.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, IL-1 is known to induce actin stress fiber formation in different cell types [60, 61], and to increase tight junction (TJ) permeability in the intestinal epithelium [62] and in the blood–brain barrier [63]. IL-1 is also involved in the non-inflammatory-related restructuring of cell junctions, which occurs during normal tissue homeostasis.…”
Section: Mechanisms Of Cytoskeletal and Cell Junctional Remodeling Bymentioning
confidence: 99%